(untitled) (Contemporary Journal of Social Science Review, 2025)
This qualitative study examines how Bapsi Sidhwa’s The Pakistani Bride represents honor killings and domestic violence as interconnected systems of patriarchal power. Using an integrated theoretical framework (postcolonial feminism, feminist violence studies, and coercive control/entrapment), the research conducts close reading and discourse-sensitive coding to identify recurring patterns of gendered oppression in narrative voice, characterization, dialogue, and the regulation of women’s space and mobility. The analysis shows that “honor” operates in the novel as a socially enforced ideology that converts women into symbols of male status and community reputation, enabling surveillance, stigma, and collective punishment. Simultaneously, domestic violence emerges as more than episodic assault; it functions as coercive control restriction, intimidation, isolation, humiliation, and threat producing fear-based compliance and limiting women’s agency. The findings argue that the novel depicts a continuum where private abuse and public honor enforcement overlap, intensifying risk when women attempt resistance or escape. By placing Sidhwa’s representation in dialogue with recent (2020–2025) scholarship on honor-based abuse and intimate partner violence, the study highlights how literature can expose the cultural language and social mechanisms that normalize gendered harm, while also tracing fragile forms of survival and micro-resistance within oppressive structures.